The Relationship between Glucose Metabolism, Resting-State fMRI BOLD Signal, and GABAA-Binding Potential: A Preliminary Study in Healthy Subjects and Those with Temporal Lobe Epilepsy - Allison C. Nugent; Ashley R. Martinez; Alana D'Alfonso; Carlos A. Zarate; William H. Theodore (2015)
Glucose metabolism has been associated with magnitude of blood oxygen level-dependent (BOLD) signal and connectivity across subjects within the default mode and dorsal attention networks. Similar correlations within subjects across the entire brain remain unexplored. [ 18 F]-fluorodeoxyglucose positron emission tomography ([ 18 F]-FDG PET), [ 11 C]-flumazenil PET, and resting-state functional magnetic resonance imaging (fMRI) scans were acquired in eight healthy individuals and nine with temporal lobe epilepsy (TLE). Regional metabolic rate of glucose (rMRGlu) was correlated with amplitude of low frequency fluctuations (ALFFs) in the fMRI signal, global fMRI connectivity (GC), regional homogeneity (ReHo), and gamma-aminobutyric acid A—binding potential (GABA A BP ND ) across the brain. Partial correlations for ALFFs, GC, and ReHo with GABA A BP ND were calculated, controlling for rMRGlu. In healthy subjects, significant positive correlations were observed across the brain between rMRGlu and ALFF, ReHo and GABA A BP ND , and between ALFFs and GABA A BP ND , controlling for rMRGlu. Brain-wide correlations between rMRGlu and ALFFs were significantly lower in TLE patients, and correlations between rMRGlu and GC were significantly greater in TLE than healthy subjects. These results indicate that the glutamatergic and GABAergic systems are coupled across the healthy human brain, and that ALFF is related to glutamate use throughout the healthy human brain. TLE may be a disorder of altered long-range connectivity in association with glutamate function.